Degradation Pathways of Cobalt‐Free LiNiO2 Cathode in Lithium Batteries. (21st December 2022) - Pan, Ruijun; Jo, Eunmi; Cui, Zehao; Manthiram, Arumugam
Abstract: Electrode‐electrolyte reactivity (EER) and particle cracking (PC) are considered two main causes of capacity fade in high‐nickel layered oxide cathodes in lithium‐based batteries. However, whether EER or PC is more critical remains debatable. Herein, the fundamental correlation between EER and PC is systematically investigated with LiNiO2 (LNO), the ultimate cobalt‐free lithium layered oxide cathode. Specifically, EER is found more critical than secondary particle cracking (SPC) in determining the cycling stability of LNO; EER leads to primary particle cracking, but mitigates SPC due to the inhibition of H2‐H3 phase transformation. Two surface degradation pathways are identified for cycled LNO under low and high EERs. A common blocking surface reconstruction layer (SRL) containing electrochemically‐inactive Ni3 O4 spinel and NiO rock‐salt phases is formed on LNO in an electrolyte with a high EER; in contrast, an electrochemically‐active SRL featuring regions of electron‐ and lithium‐ion‐conductive LiNi2 O4 spinel phase is formed on LNO in an electrolyte with a low EER. These findings unveil the intrinsic degradation pathways of LNO cathode and are foreseen to provide new insights into the development of lithium‐based batteries with a minimized EER and a maximized service life. Abstract : High electrode‐electrolyte reactivity (EER) leads to severe primary particle cracking (PPC), formation of Li + /electron blocking surface reconstruction layer (SRL), suppressed H2‐H3 phase transformation, but less secondary particle cracking (SPC), while low EER results in little PPC, formation of Li + /electron conductive SRL, retention of H2‐H3 phase transformation, in spite of more SPC.